Renal Effects Following Introduction of Cryopreserved Placental Extract on the Background of Experimental Renal Failure - Yurchenko, Tatyana N.; Kondakov, Igor I.; Strona, Vera I. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(1):75–78.